Buna-credinţă în contracte. Funcţia interpretativă a bunei-credinţe/ Good Faith in Contracts. The Interpretative Function of Good Faith - Sorin-Claude MODREANU (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice, 2025)
Good-faith is one of the four cardinal legal-moral values of law, together with free will, equity and the obligation to love one's neighbor. With its roots in Roman law, the definition, specific content, effects and functions of this concept have been the subject of extensive debate and study, and it is still not a subject that can be considered exhausted. From the point of view of the functions of good faith in a contractual context, the interpretative function requires detailed analysis. The main meaning of this function is given by the need to interpret contracts according to the real common intention of the parties. An important discussion that generates divergences in the legal literature concerns the distinction or overlap between this function and the completive function of good faith. In concrete terms, it is necessary to determine to what extent the concept of good faith should and can be used as a rule of contractual interpretation, without this activity turning into a completive operation carried by the judge.